Difficulites and some suggested solutions in teaching English to grade one students in Hadong district, Hanoi - Đỗ, Thị Phương Thúy (ĐHNN, 2017)
Chapter one: Introduction. This chapter includes rationale, aims, methods, scope of the study, and design of the thesis. Chapter two: Literaturer review. This chapter consists of theoretical background which is relevant to the purpose of the study. Chapter three: Reseach methodology. This chapter presents an introduction on the context of the primary schools in Hadong district, the subjects of the study, the instruments, the procedure for collecting data and also the methods of data analysis. Chapter four: Presentation and analysis of data. This chapter presents and analyze the data which have been collected and concluded the findings of the study. Chapter five: Suggested solutions. This chapter deals with some suggested solutions to the problems in the findings. Chapter six: Conclusions. Summary, limitations as well as suggestions for further studies and reference of the study are included in this chapter.